Meddling with Fate: The Proteasomal Deubiquitinating Enzymes. Issue 22 (10th November 2017) - de Poot, Stefanie A.H.; Tian, Geng; Finley, Daniel
Abstract: Three deubiquitinating enzymes—Rpn11, Usp14, and Uch37—are associated with the proteasome regulatory particle. These enzymes allow proteasomes to remove ubiquitin from substrates before they are translocated into the core particle to be degraded. Although the translocation channel is too narrow for folded proteins, the force of translocation unfolds them mechanically. As translocation proceeds, ubiquitin chains bound to substrate are drawn to the channel's entry port, where they can impede further translocation. Rpn11, situated over the port, can remove these chains without compromising degradation because substrates must be irreversibly committed to degradation before Rpn11 acts. This coupling between deubiquitination and substrate degradation is ensured by the Ins-1 loop of Rpn11, which controls ubiquitin access to its catalytic site. In contrast to Rpn11, Usp14 and Uch37 can rescue substrates from degradation by promoting substrate dissociation from the proteasome prior to the commitment step. Uch37 is unique in being a component of both the proteasome and a second multisubunit assembly, the INO80 complex. However, only recruitment into the proteasome activates Uch37. Recruitment to the proteasome likewise activates Usp14. However, the influence of Usp14 on the proteasome depends on the substrate, due to its marked preference for proteins that carry multiple ubiquitin chains. Usp14 exerts complex control over the proteasome, suppressing proteasome activity even when inactive in deubiquitination. A major challenge for the field will be to elucidate the specificities of Rpn11, Usp14, and Uch37 in greater depth, employing not only model in vitro substrates but also their endogenous targets. Graphical Abstract: Highlights: The three proteasomal DUBs differ strongly in mechanism, specificity, and function. Rpn11 removes ubiquitin chains from substrates that are committed to degradation. Usp14 and Uch37 can work before commitment to rescue substrates from degradation. Usp14 deubiquitinates substrates with multiple Ub modifications. Uch37 is found in both the proteasome and the INO80 chromatin remodeling complex.